Exploring Outcomes of a Targeted Supervisory Training Curriculum on Developing Multicultural Competency and Social Justice Advocacy. (December 2015) - Cook, Amy L.; Hayden, Laura A.; Gracia, Robert; Tyrrell, Rachel
Although there is extensive literature addressing the need to incorporate multicultural competency and social justice advocacy training in school counseling coursework, there are few empirical studies that have examined outcomes of incorporating such curriculum into field placement course work. Qualitative content analysis was employed to examine the use of targeted instruction on developing multicultural competency and social justice advocacy with a sample of 21 counseling students during a school practicum placement. Analyses of semi-structured interviews suggested the potential benefit of infusing targeted instruction on multicultural competency and social justice advocacy. Implications for counselor training and research are provided.